ANALISIS SURVIVAL MENGGUNAKAN METODE REGRESI COX PASIEN PENDERITA TIFUS DI RSUD SYEKH YUSUF KABUPATEN GOWA - SUJIONO, AHMAD FAUZAN RIDHA; SANUSI, WAHIDAH; SIDE, SYAFRUDDIN (E-Jurnal Matematika, 2023)
This research is a applied research with a quantitative approach that is to take or collect the necessary data and analyze it by using a model of cox regression models with proportional hazard to determine the factors that affect the rate of recovery of tifoid patient in Syekh Yusuf Hospital In Gowa. Long treatment of tifoid patient is the time of survival. In accordance with the Anderson Darling test using the software Minitab 15, the test result on the distribution of survival time of tifoid patient is Gamma Distribution. There are many factors that will affect the rate of recovery of patient such as age of the patients, patients gender, dizzy, dirty tongue, heartburn, nausea, throw up, and diarrhea. Therefore, it is important to know whatthe factors most affect the rate recovery of tifoid patient. From the result of the research using software SPSS 20, give conclusion that factors affecting of time recovery of tifoid patient in Syekh Yusuf Hospital in Gowa are age of the patients